Development of a Digital-Based Instrument to Assess Perceived Motor Competence in Children: Face Validity, Test-Retest Reliability, and Internal Consistency - Robinson, Leah E. (Sports (Basel), 2017)
Assessing children’s perceptions of their movement abilities (i.e., perceived competence) is traditionally done using picture scales—Pictorial Scale of Perceived Competence and Acceptance for Young Children or Pictorial Scale of Perceived Movement Skill Competence. Pictures fail to capture the temporal components of movement. To address this limitation, we created a digital-based instrument to assess perceived motor competence: the Digital Scale of Perceived Motor Competence. The purpose of this study was to determine the validity, reliability, and internal consistency of the Digital-based Scale of Perceived Motor Skill Competence. The Digital-based Scale of Perceived Motor Skill Competence is based on the twelve fundamental motor skills from the Test of Gross Motor Development-2nd Edition with a similar layout and item structure as the Pictorial Scale of Perceived Movement Skill Competence. Face Validity of the instrument was examined in Phase I (n = 56; M(age) = 8.6 ± 0.7 years, 26 girls). Test-retest reliability and internal consistency were assessed in Phase II (n = 54, M(age) = 8.7 years ± 0.5 years, 26 girls). Intra-class correlations (ICC) and Cronbach’s alpha were conducted to determine test-retest reliability and internal consistency for all twelve skills along with locomotor and object control subscales. The Digital Scale of Perceived Motor Competence demonstrates excellent test-retest reliability (ICC = 0.83, total; ICC = 0.77, locomotor; ICC = 0.79, object control) and acceptable/good internal consistency (α = 0.62, total; α = 0.57, locomotor; α = 0.49, object control). Findings provide evidence of the reliability of the three level digital-based instrument of perceived motor competence for older children.